Lord of the Flies Love and Hatred as in Shakespeare’s Romeo and Juliet - Tini Mogea (Pusat Riset dan Inovasi Nasional, 2023)
This investigation aims to learn more about love and hatred in Shakespeare's Romeo and Juliet. This research is qualitative since the data are in the form of words rather than numbers. In collecting the data, the writer used primary and secondary sources. The primary source is the play, Romeo and Juliet. The secondary sources are books, the internet, and some relevant articles. In analyzing the data, the writer used a mimetic approach. The result shows that human beings are born to love each other. However, in Romeo and Juliet, Shakespeare portrays not only love but also hatred that destroys the lives of human beings who are falling in love with each other. Shakespeare portrays a couple who are not allowed to continue their love relationship because their families are against each other. They are not allowed to meet each other because the families hate each other. Romeo and Juliet is a tragedy written by William Shakespeare early in his career about two young star-crossed lovers whose deaths ultimately reconcile their feuding families.